L’activité étudiante durant la crise sanitaire d’un point de vue ergologique : la question des initiatives prises par rapport à un champ de contraintes préexistantes - Jean-Luc Denny; Louis Durrive (Activités)
The COVID-19 pandemic is a public health emergency. While most studies document the deleterious effects of confinement in terms of learning (increasing inequalities, dropping out, etc.), our research aims instead to highlight the beneficial effects. Conducted at the apex of the pandelic between March and June 2020, during the first confinement in France, the study aims to investigate how the rupture produced by the brutal transformation of the teaching context was able to provide experience for learners by interpreting the facts through the prism of the constraint-initiative dialectic. In keeping with Canguilhem’s anthropological point of view on human activity, the subject of the experiment is viewed according to an ergological approach (Schwartz, 2000) as a "body-self", a concept of the unity of the person living in the world and knowing through his whole being. The study mobilizes a group of eight students in their second year of an undergraduate course in Sciences of Education and Formation. The research protocol consists of two focus groups and an intermediate individual interview per student. The results document how students enter the field of constraints and take back the initiative on three levels: their relationship with teachers, their relationship with the peer group and their relationship with knowledge. Finally, we show how students experience autonomy, away from their usual benchmarks guided by teachers who are usually perceived as regulators and controllers.